SUGESTI PERILAKU MANUSIA DALAM KARYA LUKIS REALIS - SYAIFUL ROHMI, Drs. Erfahmi, M.Sn., Yasrul Sami, S.Sn., M.Sn. (Serupa The Journal of Art Education, 2017)
This work aims to describe the meaning of suggestion affects human behavior in painting realist, so as to increase public appreciation of the importance of awareness in communication, a method in the manufacture of this thesis through several stages of preparation, elaboration, synthesis, the realization of the concept, consultations with the supervisor and completion. This work provides information to the public connoisseur of art, especially painting, that a successful communication is no suggestion role in it, the suggestion could give a negative or positive impact and this can be controlled by the recipient or perpetrators of suggestion.Kata Kunci: Sugesti, seni lukis, realis